An unusual case of hoarseness of voice. (2018) - Singh, Ranjit; Sen, Tiyas; Pattari, Sanjeev
Abstract: Amyloidosis is a condition wherein there is an over-expression of specific proteins culminating in the extracellular deposition of insoluble beta pleated sheets of fibres. These deposits disrupt function of the target organ. Its aetiology remains unknown. Primary Amyloidosis localized to the trachea and bronchus is a rare entity. It produces tumour like lesion in the tracheo-bronchial tree. We hereby discuss a patient who presented with persistent hoarseness of voice who was referred to a tertiary care centre to rule out malignancy.